Species diversity of saprophagous flies (Diptera) in hospital grounds of Tehran, Iran - Abbas Ali Mirzakhanlou; Mansoureh Shayeghi; Hassan Vatandoust; Arman Izadian; Zahra Karimi; Kamran Akbarzadeh (نامه انجمن حشره‌شناسی ایران)
Synanthropic flies are essential in transmitting various pathogens, producing myiasis, and their application in forensic entomology. The main objective of this study was to identify the medically important flies in the hospital grounds of Tehran. The sampling process for this cross-sectional study was carried out every two weeks on the grounds of four hospitals in Tehran, using bottle traps and insect nets from March 2020 to February 2021. The population data has been transformed by calculating square root due to huge variations among community data, and data was analyzed with Kruskal-Wallis test to estimate the temporal and spatial variation. A total of 18,613 adult flies were collected and 18 species were identified. These flies belonged to four families: Calliphoridae, Muscidae, Sarcophagidae, and Fanniidae. The most common species in each family were Calliphora vicina Robineau-Desvoidy, Muscina stabulans Fallen, Sarcophaga Africa Wiedemann, and Fannia canicularis L., respectively. Temporal variations showed that C. vicina had different seasonal activity, with peaks in colder months, while Lucilia sericata Meigen, Chrysomya albiceps (Wiedemann), and dominant species of Sarcophagidae peaked in mid-summer. Spatial distribution analysis revealed overall unity in collecting all three species of Calliphoridae in all hospital environments. The same status was observed for Muscidae and Fanniidae. The dominant species in all species of the family Sarcophagidae were active during warmer months. Sarcophaga nigriventris Meigen, 1826 is reported for the first time for Iranian fauna.